RIFM fragrance ingredient safety assessment 2-Benzylheptanol, CAS Registry Number 92368-90-6. (May 2018) - Api, A.M.; Belsito, D.; Botelho, D.; Browne, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; et al.
Highlights: 2-Benzylheptanol, safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read across and/or TTC.